A high-ductility composite adhesive for cold aluminum medicine bag and its preparation method
By using high-stretch composite adhesives in cold aluminum drug packaging, the problems of insufficient bonding ability, deep-drain resistance and flexibility of existing adhesives when used in cold aluminum drug packaging are solved, significantly improving the heat resistance and service life of the film layer, ensuring the stability and shelf life of the drug packaging.
Patent Information
- Application Number
- CN202411913530.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
AI Technical Summary
When used in cold aluminum drug packaging, the adhesive ability, deep-drain resistance and flexibility are poor, resulting in high blister breakage rate and easy to delaminate in high temperature and humidity environments in tropical areas, affecting the shelf life of the medicine.
A highly ductile composite adhesive is used, which includes bisphenol A type epoxy resin, modified epoxy resin, acrylate copolymer, modified nanosilica, coupling agent, reactive diluent, solvent and aromatic amine curing agent. Through the combination of these components, the flexibility, deep-drain resistance, bonding strength, heat resistance and moisture resistance of the adhesive are significantly improved.
It significantly reduces the film layer damage rate, improves the heat resistance of the outer layer and its service life in high temperature and high humidity environments, and ensures the stability and shelf life of the drug packaging.
Smart Images

Figure BDA0005206318220000091 
Figure BDA0005206318220000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and in particular to a highly ductile composite adhesive for cold aluminum medicine packages and a preparation method thereof. Background Art
[0002] China's pharmaceutical packaging materials industry is an emerging industry. Since the beginning of the new century, the industry has developed faster and has played a vital role in promoting the development of China's pharmaceutical industry. Pharmaceutical packaging materials have high technical content and strict quality requirements. Before October 2000, my country adopted a licensing management system for pharmaceutical packaging materials. Starting from October 2000, the original management method was changed to a registration system, and each variety was certified and registered. The gross output value of my country's pharmaceutical packaging industry has accounted for more than 10% of the national packaging industry's gross output value, which is much higher than the proportion of the entire pharmaceutical industry in the national industrial output value. Today, with new products and new drugs emerging in an endless stream, my country's pharmaceutical packaging industry has a broad market space. The quality of pharmaceutical packaging, like other commodity packaging, can directly affect the sales of drugs.
[0003] Cold stamping solid pharmaceutical composite hard tablets are commonly known as: cold aluminum / cold stamping aluminum. They have beautiful appearance, simple and generous. The cold aluminum packaging form is durable and not easy to delaminate. Color molding and printing can be used according to different needs of customers. The product is composed of NY / adhesive / Al / adhesive / PVC. Cold aluminum has excellent barrier properties, which can almost completely isolate water vapor, oxygen, ultraviolet rays, and has excellent fragrance preservation performance. Compared with traditional PVC, each blister forms an independent unit that completely isolates water vapor, oxygen, and ultraviolet rays. Taking out part of the contents of a plate of tablets will not have any effect on other intact drugs in the same plate. It can be used for the packaging of pills, tablets, powders, suppositories, capsules and external applications. It can replace PVC and is particularly suitable for packaging drugs that are sensitive to moisture or drugs that need to be sold in hot and humid areas. By changing the mold, it is very convenient to design and manufacture beautiful and diverse shapes. In addition, its unique and gorgeous appearance adds to the attractiveness of the packaged products, which can greatly promote the sales of products and has become synonymous with high-end drugs. It adopts cold pressing to eliminate the heating process, and is heat-sealed with PTP aluminum foil, making it easy to open.
[0004] It is precisely because of the above advantages of cold aluminum that it is increasingly used in pharmaceutical blister packaging. The adhesive used in its structure is crucial to the deep drawing, heat resistance and use of cold aluminum in tropical areas. The current adhesives have poor bonding ability, deep drawing resistance and flexibility, resulting in the following problems with this composite film: when large packages are deep drawn, the blister breakage rate is high; due to the general high temperature and high humidity resistance of the adhesive layer, when used in tropical areas with high humidity, the packaging is prone to stratification, thus affecting the shelf life of the medicine. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present application provides a highly ductile composite adhesive for cold aluminum medicine packages and a preparation method thereof. The highly ductile composite adhesive for cold aluminum medicine packages prepared in the present application has excellent flexibility, deep drawing resistance and bonding strength. It also exhibits excellent heat resistance and moisture resistance. The composite adhesive prepared in the present application can be used in cold stamping aluminum packaging materials to significantly reduce the film breakage rate, improve the heat resistance of the outer layer, and the service life in high temperature and high humidity environments.
[0006] In the first aspect, the present application provides a highly ductile composite adhesive for cold aluminum medicine packs, which adopts the following technical solution: A highly ductile composite adhesive for cold aluminum medicine packages comprises the following raw materials, calculated by weight: 18-26 parts of bisphenol A epoxy resin E-51, 7-12 parts of modified epoxy resin, 6-8 parts of acrylate copolymer, 8-12 parts of modified nano-silicon dioxide, 0.5-0.8 parts of coupling agent, 4-6 parts of active diluent, 40-50 parts of solvent, and 10-13 parts of aromatic amine curing agent.
[0007] By adopting the above technical solutions, bisphenol A epoxy resin E-51: As one of the main components of the composite adhesive, it provides good strength and bonding properties. The benzene ring, hydroxyl group, ether group and epoxy group in its structure give the product excellent physical and chemical properties. Modified epoxy resin: The polyurethane-modified epoxy resin increases the flexibility and heat resistance of the composite adhesive, while solving the problem of heat-resistant delamination. This modification significantly improves the flexibility, bonding performance and deep drawing resistance of the adhesive. Acrylate copolymer: It provides good bonding and flexibility, further enhancing the flexibility, deep drawing resistance and bonding strength of the composite adhesive. Modified nano-silica: After modification by γ-aminopropyltriethoxysilane, its dispersibility and compatibility are significantly improved. This modification not only enhances the thermal conductivity of the composite adhesive, but also improves its heat resistance and moisture resistance. Coupling agent and reactive diluent: Coupling agent is used to improve the compatibility between the components, while reactive diluent is used to adjust the viscosity of the adhesive, making it easier to apply and cure. Solvent and aromatic amine curing agent: Solvent is used to adjust the viscosity of the adhesive to make it suitable for application; aromatic amine curing agent is a curing agent used to promote the curing reaction of bisphenol A epoxy resin to form a cured product with good physical and chemical properties. The combined effect of these components gives the composite adhesive excellent flexibility, deep drawing resistance, bonding strength, heat resistance and moisture resistance. In the application of cold stamping aluminum packaging materials, this composite adhesive can significantly reduce the breakage rate of the film layer, improve the heat resistance of the outer layer and the service life in high temperature and high humidity environments.
[0008] Preferably, the mass ratio of the bisphenol A epoxy resin to the modified epoxy resin is 2:1.
[0009] By adopting the above technical solutions, bisphenol A epoxy resin E-51: This resin has excellent mechanical properties and chemical stability, and can provide good bonding strength and heat resistance. At the same time, its cured product usually has good strength. Modified epoxy resin: Epoxy resin modified by polyurethane can provide additional flexibility and heat resistance. This modified resin can solve the problem of heat-resistant delamination of composite adhesives, while significantly improving the flexibility, bonding performance and deep drawing resistance of composite adhesives. When the mass ratio of bisphenol A epoxy resin and modified epoxy resin is 2:1, this ratio may be intended to balance the mechanical properties and flexibility of the composite adhesive. Bisphenol A epoxy resin provides the necessary bonding strength and heat resistance, while the modified epoxy resin increases flexibility, making the composite adhesive perform well in application scenarios requiring flexibility and deep drawing resistance. At the same time, this ratio may also help solve the problem of heat-resistant delamination because the addition of modified epoxy resin can provide better heat resistance. In general, the synergy between bisphenol A epoxy resin and modified epoxy resin may include providing excellent bond strength, heat resistance and flexibility while solving the problem of heat-resistant delamination.
[0010] Preferably, the modified epoxy resin comprises the following raw materials in parts by mass: 5-30 parts of bisphenol A epoxy resin E-442, 20-30 parts of hexamethylene diisocyanate, 0.05-0.1 parts of monobutyl tin triisooctanoate, 5-8 parts of n-dodecyl alcohol, and 20-30 parts of polypropylene glycol diglycidyl ether.
[0011] Preferably, the preparation method of the modified epoxy resin is as follows: according to the mass fractions, bisphenol A epoxy resin E-44 and monobutyl tin triisooctanoate are added to a reaction kettle, vacuum dehydration is carried out for 2-3 hours, hexamethylene diisocyanate is added, and the reaction is carried out at 80° C. for 3-4 hours; when the residual NCO is close to 0, polypropylene glycol diglycidyl ether and n-dodecyl alcohol are added in a formula ratio, the reaction is continued for 3-4 hours, the temperature is reduced to below 30° C., and the material is discharged to obtain the modified epoxy resin.
[0012] By adopting the above technical scheme, firstly, the modified epoxy resin is obtained by reacting bisphenol A epoxy resin E-44 with other raw materials. Among them, bisphenol A epoxy resin E-44 has good strength and adhesion. At the same time, by adding raw materials such as hexamethylene diisocyanate and polypropylene glycol diglycidyl ether, the modified epoxy resin has better flexibility and heat resistance. Secondly, the role of modified epoxy resin in composite adhesives is mainly reflected in the following aspects: 1. Increase flexibility: The modified epoxy resin contains polyurethane segments, which makes the composite adhesive have better flexibility and can adapt to complex shapes and surface conditions. 2. Improve heat resistance: The modified epoxy resin has good heat resistance and can improve the stability of the composite adhesive in high temperature environment. 3. Enhance bonding performance: The modified epoxy resin has strong bonding force and can significantly improve the bonding strength of the composite adhesive. 4. Solve the problem of heat-resistant delamination: The modified epoxy resin can effectively solve the delamination problem of the composite adhesive in a high temperature environment and improve its service life. In summary, modified epoxy resin plays an important role in composite adhesives. It not only improves the flexibility, heat resistance and bonding strength of composite adhesives, but also solves the problem of heat-resistant delamination.
[0013] Preferably, the method for preparing the acrylic acid ester copolymer comprises the following steps: S51, according to the mass fractions, 8 parts of sodium lauryl sulfate, 20 parts of polyvinyl alcohol and 10 parts of hexadecanol were mixed with 300 parts of deionized water, and heated at 65° C. with stirring at 200 rpm to obtain a mixed dispersion solution after being fully dissolved; S52, according to the mass parts, 650 parts of acrylonitrile, 300 parts of ethyl acrylate, 50 parts of acrylic acid and 10 parts of initiator dodecyl peroxide were stirred at 300 rpm to obtain a uniform monomer solution; S53, adding the homogeneous monomer solution to the mixed dispersed solution, and then emulsifying at a high speed of 9000 rpm for 5-10 min to obtain a microsuspension; S54. According to the mass fraction, nitrogen is passed through the microsuspension reactor for 30 minutes, the temperature is raised to 70°C for reaction for 3-4 hours, and then the temperature is raised to 85°C for reaction for 3-4 hours. After the reaction is completed, an appropriate amount of ammonia water is added to neutralize to pH 7, the product is filtered, and the obtained polymer emulsion is spray-dried to obtain a solid powder. The solid powder is washed with deionized water, dried, crushed, and sieved to obtain an acrylic copolymer.
[0014] By adopting the above technical solution, the prepared acrylic copolymer has good adhesion and flexibility, and is used in composite adhesives to significantly improve the flexibility, deep drawing resistance and bonding strength of the composite adhesives.
[0015] Preferably, the preparation method of the modified nano-silica is as follows: 100 parts of nano-silica with an average particle size of 20-30 nanometers are dispersed in a solution consisting of 200 parts of ethanol and 50 parts of water, and then 1-2 parts of γ-aminopropyltriethoxysilane are added thereto, the pH of the solution is adjusted to 5-6, stirred for 2-3 hours, and centrifuged, washed, and dried to obtain the modified nano-silica.
[0016] By adopting the above technical solutions, modified nano-silica can improve the thermal conductivity of the composite adhesive, making it more stable at high temperatures. Through the modification of γ-aminopropyltriethoxysilane, the heat resistance of nano-silica is improved, thereby enhancing the heat resistance of the entire composite adhesive. The modified nano-silica has better dispersibility and stronger compatibility in organic polymers, which helps to form a more uniform composite material structure. Due to the addition of nano-silica, the bonding strength and flexibility of the composite adhesive are significantly improved, which is particularly important for the application of cold stamping aluminum packaging materials. It can reduce the breakage rate of the film layer, improve the heat resistance of the outer layer and the service life in high temperature and high humidity environments.
[0017] Preferably, the coupling agent is composed of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropylmethyldiethoxysilane in a mass ratio of 3:4:1-3.
[0018] By adopting the above technical scheme, the coupling agent can improve the compatibility between inorganic fillers (such as nano-silica) and organic polymers (such as epoxy resin), thereby enhancing the interfacial bonding between them. This is crucial to improving the overall performance of the composite adhesive. By using a coupling agent, the dispersibility of nano-silica in the resin matrix can be improved, and the occurrence of agglomeration can be avoided, thereby improving the uniformity and performance of the composite material. The coupling agent can react with the hydroxyl group on the surface of nano-silica to form a stable chemical bond, which helps to improve the heat resistance and moisture resistance of the composite adhesive. The addition of a coupling agent can increase the flexibility and deep drawing resistance of the composite adhesive, which is particularly important for the application of cold stamping aluminum packaging materials because it can reduce material breakage during the forming process. 5. Improve bonding performance: The use of a coupling agent can also improve the bonding performance of the composite adhesive, making it more firm and less likely to fall off when bonding aluminum materials. The γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropylmethyldiethoxysilane of the present application are composed of a mass ratio of 3:4:1-3, and this specific ratio may be optimized to ensure the best performance balance. The combined use of these three coupling agents may have a synergistic effect, which can not only provide the advantages of the above-mentioned single coupling agent, but also may produce additional performance improvements. In short, the coupling agent plays a vital role in this application. It not only improves the performance of the composite adhesive, but also ensures its reliability and durability in practical applications.
[0019] Preferably, the aromatic amine curing agent is composed of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane in a mass ratio of 3:4.
[0020] By adopting the above technical scheme, the curing agent plays a catalytic and promoting role in the curing process of epoxy resin, so that the epoxy resin is converted from liquid to solid. Aromatic amine curing agents are often used as epoxy resin curing agents due to their high reactivity and good heat resistance. The aromatic amine curing agent is composed of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane, and this combination may help to improve the speed and efficiency of the curing reaction. The ratio of diaminodiphenylmethane to 3,3-diethyl-4,4-diaminodiphenylmethane is 3:4, and this specific ratio may help to balance the reactivity and heat resistance of the curing agent. Diaminodiphenylmethane may provide higher reactivity, while 3,3-diethyl-4,4-diaminodiphenylmethane may increase the heat resistance of the cured product. This combination may help to optimize the curing process and improve the performance of the final product. The selection and proportion of aromatic amine curing agents directly affect the curing performance and final performance of the composite adhesive. The appropriate curing agent can ensure that the composite adhesive maintains good adhesion and heat resistance during the curing process, while improving its service life in high temperature and high humidity environments. In summary, the selection of aromatic amine curing agent and the ratio between the components are crucial to the performance of the composite adhesive. Accurately controlling the ratio of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane can significantly improve the curing efficiency and heat resistance of the composite adhesive, thereby meeting the application requirements of cold stamping aluminum packaging materials.
[0021] Preferably, the active diluent is butyl glycidyl ether, and the solvent is butanone.
[0022] In the second aspect, the present application provides a method for preparing a highly ductile composite adhesive for cold aluminum medicine packs, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned high-ductility composite adhesive for cold aluminum medicine packs, comprising the following steps: S101, according to the mass fraction, add two-thirds of the solvent and active diluent into the reaction kettle, heat to 30-40°C and stir, add bisphenol A epoxy resin E-51, modified epoxy resin and acrylic copolymer to completely dissolve; then add modified nano-silica and coupling agent, rotate at 300rpm, control the temperature below 50°C, maintain the vacuum degree at 0.07MPa, stir for 30-40min, and cool to 30°C to obtain a mixture; S102. Add the aromatic amine curing agent to the remaining solvent for dilution according to the mass fraction, stir evenly, then add it to the mixture, stir evenly, and obtain a highly ductile composite adhesive for cold aluminum medicine packages.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. Improved flexibility of composite adhesives: By adding modified epoxy resins and acrylate copolymers, the flexibility of composite adhesives has been significantly improved. This is particularly important for the application of cold stamped aluminum packaging materials, as it can maintain the integrity of shape and structure when subjected to impact or pressure.
[0024] 2. Enhanced deep drawing resistance: The addition of modified epoxy resin and acrylate copolymer not only improves the flexibility of the composite adhesive, but also enhances its deep drawing resistance. This means that when subjected to severe impact or stretching, the composite adhesive can better maintain its bonding performance and structural stability.
[0025] 3. Improved bonding strength: The addition of modified epoxy resin and acrylate copolymer significantly improves the bonding strength of the composite adhesive. This is crucial to ensure the sealing and protective properties of aluminum packaging materials.
[0026] 4. Enhanced heat resistance and moisture resistance: The addition of modified nano-silica enhances the thermal conductivity and heat resistance of the composite adhesive. At the same time, the nano-silica modified by γ-aminopropyltriethoxysilane improves the dispersibility and compatibility of the composite adhesive, and further improves its heat resistance and moisture resistance. This is of great significance for maintaining the performance and service life of aluminum packaging materials in high temperature and high humidity environments.
[0027] 5. Reduce the film breakage rate: The application of composite adhesives can significantly reduce the film breakage rate of cold-stamped aluminum packaging materials, which is of great significance for improving product quality and reliability. DETAILED DESCRIPTION
[0028] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0029] In the following examples and preparation examples, 1 part means 100 g.
[0030] Preparation Example 1 Preparation of modified epoxy resin The modified epoxy resin comprises the following raw materials in parts by weight: 28 parts of bisphenol A epoxy resin E-44, 24 parts of hexamethylene diisocyanate, 0.07 parts of monobutyl tin triisooctanoate, 7 parts of n-dodecyl alcohol, and 25 parts of polypropylene glycol diglycidyl ether. The preparation method of the modified epoxy resin is as follows: according to the parts by weight, bisphenol A epoxy resin E-44 and monobutyl tin triisooctanoate are added into a reaction kettle, vacuum dehydration is performed for 2.5 hours, hexamethylene diisocyanate is added, and the reaction is performed at 80° C. for 3.5 hours; when the residual NCO is close to 0, polypropylene glycol diglycidyl ether and n-dodecyl alcohol in a formula ratio are added, the reaction is continued for 3.5 hours, the temperature is lowered to below 30° C., and the material is discharged to obtain the modified epoxy resin.
[0031] Preparation Example 2 Preparation of acrylic acid ester copolymer The preparation method of the acrylic acid ester copolymer comprises the following steps: S51, according to the mass fractions, 8 parts of sodium lauryl sulfate, 20 parts of polyvinyl alcohol and 10 parts of hexadecanol were mixed with 300 parts of deionized water, and heated at 65° C. with stirring at 200 rpm to obtain a mixed dispersion solution after being fully dissolved; S52, according to the mass parts, 650 parts of acrylonitrile, 300 parts of ethyl acrylate, 50 parts of acrylic acid and 10 parts of initiator dodecyl peroxide were stirred at 300 rpm to obtain a uniform monomer solution; S53, adding the homogeneous monomer solution to the mixed dispersed solution, and then emulsifying at a high speed of 9000 rpm for 8 minutes to obtain a microsuspension; S54. According to the mass fraction, nitrogen is passed through the microsuspension reactor for 30 minutes, the temperature is raised to 70°C for reaction for 3.5 hours, and then the temperature is raised to 85°C for reaction for 3.5 hours. After the reaction is completed, an appropriate amount of ammonia water is added to neutralize to pH 7, the product is filtered, and the obtained polymer emulsion is spray-dried to obtain a solid powder. The solid powder is washed with deionized water, dried, crushed, and sieved to obtain an acrylic copolymer.
[0032] Preparation Example 3 Preparation of modified nano-silicon dioxide The preparation method of modified nano-silica comprises the following steps: dispersing 100 parts of nano-silica with an average particle size of 20 nanometers in a solution consisting of 200 parts of ethanol and 50 parts of water according to the mass fraction, and then adding 1.5 parts of γ-aminopropyltriethoxysilane thereto, adjusting the pH of the solution to 5.6, stirring for 2.3 hours, and obtaining modified nano-silica through centrifugation, washing, and drying.
[0033] Example 1 A highly ductile composite adhesive for cold aluminum medicine packs, comprising the following raw materials by weight: 18 parts of bisphenol A epoxy resin E-51, 7 parts of modified epoxy resin, 6 parts of acrylate copolymer, 8 parts of modified nano-silicon dioxide, 0.5 parts of coupling agent, 4 parts of butyl glycidyl ether, 40 parts of butanone, and 10 parts of aromatic amine curing agent, wherein the coupling agent is composed of γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethyl (ethyl) silane and γ-aminopropyl methyl diethoxy silane in a weight ratio of 3:4:1, and the aromatic amine curing agent is composed of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane in a weight ratio of 3:4; The method for preparing the above-mentioned high-ductility composite adhesive for cold aluminum medicine packs comprises the following steps: S101. Add two-thirds of butanone and butyl glycidyl ether into a reaction kettle according to their mass fractions, heat to 30° C. and stir, add bisphenol A epoxy resin E-51, modified epoxy resin and acrylic copolymer to completely dissolve; then add modified nano-silica and coupling agent, rotate at 300 rpm, control the temperature below 50° C., maintain the vacuum degree at 0.07 MPa, stir for 30 min, and cool to 30° C. to obtain a mixture; S102. Dilute the aromatic amine curing agent into the remaining butanone according to the mass fraction, stir evenly, then add it into the mixture, stir evenly, and obtain a highly ductile composite adhesive for cold aluminum medicine packages.
[0034] Example 2 A highly ductile composite adhesive for cold aluminum medicine packs, comprising the following raw materials by weight: 26 parts of bisphenol A epoxy resin E-51, 12 parts of modified epoxy resin, 8 parts of acrylate copolymer, 12 parts of modified nano-silica, 0.8 parts of coupling agent, 6 parts of butyl glycidyl ether, 50 parts of butanone, and 13 parts of aromatic amine curing agent, wherein the coupling agent is composed of γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethyl (ethyl) silane and γ-aminopropyl methyl diethoxy silane in a weight ratio of 3:4:3, and the aromatic amine curing agent is composed of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane in a weight ratio of 3:4; The method for preparing the above-mentioned high-ductility composite adhesive for cold aluminum medicine packs comprises the following steps: S101. Add two-thirds of butanone and butyl glycidyl ether into a reaction kettle according to their mass fractions, heat to 40°C and stir, add bisphenol A epoxy resin E-51, modified epoxy resin and acrylic copolymer and completely dissolve them; then add modified nano-silica and coupling agent, rotate at 300 rpm, control the temperature below 50°C, maintain the vacuum degree at 0.07 MPa, stir for 40 minutes, and cool to 30°C to obtain a mixture; S102. Dilute the aromatic amine curing agent into the remaining butanone according to the mass fraction, stir evenly, then add it into the mixture, stir evenly, and obtain a highly ductile composite adhesive for cold aluminum medicine packages.
[0035] Example 3 A highly ductile composite adhesive for cold aluminum medicine packs, comprising the following raw materials by weight: 24 parts of bisphenol A epoxy resin E-51, 9 parts of modified epoxy resin, 7 parts of acrylate copolymer, 10 parts of modified nano-silica, 0.7 parts of coupling agent, 5 parts of butyl glycidyl ether, 45 parts of butanone, and 11.6 parts of aromatic amine curing agent, wherein the coupling agent is composed of γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethyl (ethyl) silane and γ-aminopropyl methyl diethoxy silane in a weight ratio of 3:4:2, and the aromatic amine curing agent is composed of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane in a weight ratio of 3:4; The method for preparing the above-mentioned high-ductility composite adhesive for cold aluminum medicine packs comprises the following steps: S101. Add two-thirds of butanone and butyl glycidyl ether into a reaction kettle according to their mass fractions, heat to 35° C. and stir, add bisphenol A epoxy resin E-51, modified epoxy resin and acrylic copolymer to completely dissolve; then add modified nano-silica and coupling agent, rotate at 300 rpm, control the temperature below 50° C., maintain the vacuum degree at 0.07 MPa, stir for 35 min, and cool to 30° C. to obtain a mixture; S102. Dilute the aromatic amine curing agent into the remaining butanone according to the mass fraction, stir evenly, then add it into the mixture, stir evenly, and obtain a highly ductile composite adhesive for cold aluminum medicine packages.
[0036] Example 4 The same as Example 3, except that: 22 parts of bisphenol A epoxy resin E-51 and 11 parts of modified epoxy resin.
[0037] Comparative Example 1 The same as Example 4, except that: 33 parts of bisphenol A epoxy resin E-51 and 0 parts of modified epoxy resin.
[0038] Comparative Example 2 The same as Example 4, except that an equal amount of ethyl acrylate is used instead of the acrylic ester copolymer.
[0039] Comparative Example 3 The same as Example 4, except that an equal amount of nano-silicon dioxide with an average particle size of 20 nanometers is used instead of the modified nano-silicon dioxide.
[0040] Comparative Example 4 The same as Example 4, except that: the coupling agent is γ-aminopropyltriethoxysilane.
[0041] Comparative Example 5 The same as Example 4, except that: the coupling agent is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0042] Comparative Example 6 The same as Example 4, except that: the coupling agent is γ-aminopropylmethyldiethoxysilane.
[0043] Comparative Example 7 The same as Example 4, except that: the aromatic amine curing agent is diaminodiphenylmethane.
[0044] Comparative Example 8 The same as Example 4, except that: the aromatic amine curing agent is 3,3-diethyl-4,4-diaminodiphenylmethane.
[0045] Performance testing The above-mentioned Examples 1 to 3 and Comparative Examples 1 to 8 were respectively used to prepare high-ductility composite adhesive samples for cold aluminum medicine packages, coated on both sides of the aluminum foil, and baked in an oven at 90°C for 20 minutes. After drying, the thickness of the adhesive layer was about 6 microns. Then, the inner side NY (nylon) and the outer side PVC were bonded and aged, and the following tests were performed. The results are shown in Table 1.
[0046] Peel strength (according to the provisions of B / T 8808-1988 "Peel test method for soft composite plastic materials"): the sample width is a long strip of 15mm, and the test speed is 100mm / min; High temperature peeling test: refer to the peeling strength test method and test the specimen at 120℃; Deep punching performance test: Use a double-pit deep punching die with a distance of 1mm between the two pits, punch at different depths, and observe whether there are abnormal phenomena such as delamination and whitening at the edges and corners of the outer film after deep punching. The maximum depth of delamination and whitening is the deep punching depth; Heat resistance test (put the sample into a 180℃ oven after punching to a depth of 7.5mm for heat resistance test, take out the sample after 20S to observe whether bubbling / delamination of the aluminum foil occurs); Double 85 moisture and heat resistance (B / T 2423.50 (1000h), moisture and heat aging resistance: Place the sample with a punching depth of 7.5mm in a constant temperature and humidity chamber at a temperature of 85℃ and a relative humidity of 85% for 1000h, and check the appearance of the sample to see if the aluminum foil has bubbling / delamination.
[0047] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The highly ductile composite adhesive for cold aluminum medicine packaging prepared in Examples 1 to 4 has excellent flexibility, deep drawing resistance and bonding strength. It also exhibits excellent heat resistance and moisture resistance. The composite adhesive prepared in this application can be used in cold stamping aluminum packaging materials to significantly reduce the film layer breakage rate, improve the heat resistance of the outer layer, and the service life in high temperature and high humidity environments.
[0048] 2) The performance comparison analysis of the high-ductility composite adhesive for cold aluminum medicine package prepared in Example 4 and Example 3 shows that when the mass fraction ratio of bisphenol A epoxy resin and modified epoxy resin is 2:1, this ratio may be intended to balance the mechanical properties and flexibility of the composite adhesive. The synergy between bisphenol A epoxy resin and modified epoxy resin can provide excellent bonding strength, heat resistance and flexibility, while solving the problem of heat-resistant delamination.
[0049] 3) The performance comparison analysis of the high-ductility composite adhesive for cold aluminum medicine packages prepared in Example 4 and Comparative Example 1 shows that the modified epoxy resin prepared in this application has better flexibility and heat resistance. The modified epoxy resin contains polyurethane segments, which makes the composite adhesive have better flexibility and can adapt to complex shapes and surface conditions. The modified epoxy resin has good heat resistance and can improve the stability of the composite adhesive in a high temperature environment. The modified epoxy resin has strong adhesion and can significantly improve the bonding strength of the composite adhesive. The modified epoxy resin can effectively solve the delamination problem of the composite adhesive in a high temperature environment and improve its service life.
[0050] 4) The performance comparison analysis of the high-ductility composite adhesive for cold aluminum medicine packages prepared in Example 4 and Comparative Example 2 shows that the addition of the acrylic copolymer prepared in this application has good adhesion and flexibility, and its application in the composite adhesive can significantly improve the flexibility, deep drawing resistance and bonding strength of the composite adhesive.
[0051] 5) The performance comparison analysis of the high-ductility composite adhesive for cold aluminum medicine packages prepared in Example 4 and Comparative Example 3 shows that the addition of modified nano-silica significantly improves the bonding strength and flexibility of the composite adhesive, which is particularly important for the application of cold stamping aluminum packaging materials. It can reduce the breakage rate of the film layer, improve the heat resistance of the outer layer and the service life in high temperature and high humidity environments.
[0052] 6) The performance comparison analysis of the high-ductility composite adhesive for cold aluminum medicine package prepared by Example 4 and Comparative Examples 4-6 shows that the coupling agent is composed of γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxy (ethyl) silane and γ-aminopropyl methyl diethoxy silane in a mass ratio of 3:4:2. The coupling agent can improve the compatibility between inorganic fillers (such as nano-silicon dioxide) and organic polymers (such as epoxy resins), thereby enhancing the interfacial bonding between them. This is crucial to improving the overall performance of the composite adhesive. By using a coupling agent, the dispersibility of nano-silicon dioxide in the resin matrix can be improved, and the occurrence of agglomeration can be avoided, thereby improving the uniformity and performance of the composite material. The combined effect of γ-aminopropyl triethoxy silane, N-(β-aminoethyl)-γ-aminopropyl trimethoxy (ethyl) silane and γ-aminopropyl methyl diethoxy silane can significantly improve the comprehensive performance of the adhesive composition.
[0053] 7) The performance comparison analysis of the highly ductile composite adhesive for cold aluminum medicine packs prepared in Example 4 and Comparative Examples 7-8 shows that the aromatic amine curing agent is composed of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane in a mass ratio of 3:4, and the curing agent plays a catalytic and promoting role in the curing process of the epoxy resin, so that the epoxy resin is converted from a liquid to a solid state. The combined effect between diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane can significantly improve the comprehensive performance of the adhesive composition.
[0054] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A highly ductile composite adhesive for cold aluminum medicine packs, characterized in that: The preparation raw materials include the following by weight: 18-26 parts of bisphenol A epoxy resin E-51, 7-12 parts of modified epoxy resin, 6-8 parts of acrylic copolymer, 8-12 parts of modified nano silicon dioxide, 0.5-0.8 parts of coupling agent, 4-6 parts of active diluent, 40-50 parts of solvent and 10-13 parts of aromatic amine curing agent.
2. According to claim 1, a highly ductile composite adhesive for cold aluminum medicine packs, characterized in that: The mass ratio of the bisphenol A epoxy resin to the modified epoxy resin is 2:
1.
3. According to claim 1, a highly ductile composite adhesive for cold aluminum medicine packs, characterized in that: The modified epoxy resin comprises the following raw materials in parts by weight: 25-30 parts of bisphenol A epoxy resin E-44, 20-30 parts of hexamethylene diisocyanate, 0.05-0.1 parts of monobutyl tin triisooctanoate, 5-8 parts of n-dodecyl alcohol, and 20-30 parts of polypropylene glycol diglycidyl ether.
4. According to claim 3, a highly ductile composite adhesive for cold aluminum medicine packs, characterized in that: The preparation method of the modified epoxy resin is as follows: according to the mass fractions, bisphenol A epoxy resin E-44 and monobutyl tin triisooctanoate are added into a reaction kettle, vacuum dehydration is performed for 2-3 hours, hexamethylene diisocyanate is added, and the reaction is performed at 80° C. for 3-4 hours; when the residual NCO is close to 0, polypropylene glycol diglycidyl ether and n-dodecyl alcohol in a formula ratio are added, the reaction is continued for 3-4 hours, the temperature is lowered to below 30° C., and the material is discharged to obtain the modified epoxy resin.
5. According to claim 1, a highly ductile composite adhesive for cold aluminum medicine packs, characterized in that: The method for preparing the acrylic acid ester copolymer comprises the following steps: S51, according to the mass fractions, 8 parts of sodium lauryl sulfate, 20 parts of polyvinyl alcohol and 10 parts of hexadecanol were mixed with 300 parts of deionized water, and heated at 65° C. with stirring at 200 rpm to obtain a mixed dispersion solution after being fully dissolved; S52, according to the mass parts, 650 parts of acrylonitrile, 300 parts of ethyl acrylate, 50 parts of acrylic acid and 10 parts of initiator dodecyl peroxide were stirred at 300 rpm to obtain a uniform monomer solution; S53, adding the homogeneous monomer solution to the mixed dispersed solution, and then emulsifying at a high speed of 9000 rpm for 5-10 min to obtain a microsuspension; S54. According to the mass fraction, nitrogen is passed through the microsuspension reactor for 30 minutes, the temperature is raised to 70°C for reaction for 3-4 hours, and then the temperature is raised to 85°C for reaction for 3-4 hours. After the reaction is completed, an appropriate amount of ammonia water is added to neutralize to pH 7, the product is filtered, and the obtained polymer emulsion is spray-dried to obtain a solid powder. The solid powder is washed with deionized water, dried, crushed, and sieved to obtain an acrylic copolymer.
6. The highly ductile composite adhesive for cold aluminum medicine packs according to claim 1, characterized in that: The preparation method of the modified nano-silicon dioxide comprises the following steps: dispersing 100 parts of nano-silicon dioxide with an average particle size of 20-30 nanometers in a solution consisting of 200 parts of ethanol and 50 parts of water according to mass fractions, then adding 1-2 parts of γ-aminopropyltriethoxysilane thereto, adjusting the pH of the solution to 5-6, stirring for 2-3 hours, centrifuging, washing and drying to obtain the modified nano-silicon dioxide.
7. The highly ductile composite adhesive for cold aluminum medicine packs according to claim 1, characterized in that: The coupling agent is composed of gamma-aminopropyltriethoxysilane, N-(beta-aminoethyl)-gamma-aminopropyltrimethoxysilane and gamma-aminopropylmethyldiethoxysilane in a mass ratio of 3:4:1-3.
8. The highly ductile composite adhesive for cold aluminum medicine packs according to claim 1, characterized in that: The aromatic amine curing agent is composed of diaminodiphenylmethane and 3,3-diethyl-4,4-diaminodiphenylmethane in a mass ratio of 3:
4.
9. The highly ductile composite adhesive for cold aluminum medicine packs according to claim 1, characterized in that: The active diluent is butyl glycidyl ether, and the solvent is butanone.
10. A method for preparing a highly ductile composite adhesive for cold aluminum medicine packs as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S101, according to the mass fraction, add two-thirds of the solvent and active diluent into the reaction kettle, heat to 30-40°C and stir, add bisphenol A epoxy resin E-51, modified epoxy resin and acrylic copolymer to completely dissolve; then add modified nano-silica and coupling agent, rotate at 300rpm, control the temperature below 50°C, maintain the vacuum degree at 0.07MPa, stir for 30-40min, and cool to 30°C to obtain a mixture; S102. Add the aromatic amine curing agent to the remaining solvent for dilution according to the mass fraction, stir evenly, then add it to the mixture, stir evenly, and obtain a highly ductile composite adhesive for cold aluminum medicine packages.